Association between Maternal Pelvis Height and Intrapartum Foetal Head Moulding in Ugandan Mothers with Spontaneous Vertex Deliveries - Ian G. Munabi; Samuel Abilemech Luboga; Livingstone Luboobi; Florence Mirembe (Obstetrics and Gynecology International)
Introduction. In Sub-Saharan Africa, excessive foetal head moulding is commonly associated with cephalopelvic disproportion and obstructed labour. This study set out to determine the associations of maternal pelvis height and maternal height with intrapartum foetal head moulding. Methods. This was a multisite secondary analysis of maternal birth records of mothers with singleton pregnancies ending in a spontaneous vertex delivery. A summary of the details of the pregnancy and delivery records were reviewed and analysed using multilevel logistic regression respect to foetal head moulding. The alpha level was set at P<0.05. Results. 412 records were obtained, of which 108/385 (28%) observed foetal head moulding. There was a significant reduction in risk of foetal head moulding with increasing maternal height (Adj. IRR 0.97, P=0.05), maternal pelvis height (Adj. IRR 0.88, P<0.01), and raptured membranes (Adj. IRR 0.10, P<0.01). There was a significant increased risk of foetal head moulding with increasing birth weight (Adj. IRR 1.90, P<0.01) and duration of monitored active labour (Adj. IRR 1.21, P<0.01) in the final model. Conclusion. This study showed that increasing maternal height and maternal pelvis height were associated with a significant reduction in intrapartum foetal head moulding.